ANALISIS FAKTOR INTERNAL DAN EKSTERNAL BISNIS YANG MEMPENGARUHI DAYA SAING UKM SONGKOK KABUPATEN GRESIK - Narto Narto (Universitas Putera Batam, 2019)
One of the supporters of the growth of the Indonesian economy is the small and medium business sector. To increase contributions to national economic growth, SMEs must play an active role in business development to improve competitiveness. SME development must consider internal and external factors as the basis for determining strategies so that they can make a significant contribution in accelerating economic improvement. UKM Songkok Gresik has great potential in improving the economy of the surrounding community. Some of the obstacles faced include the difficulty of procuring raw materials and uncertain market conditions which greatly affect the existence of SME Songkok Gresik. This study aims to determine internal and external factors that affect competitiveness of small and medium enterprises making Songkok in Gresik Regency. The results of the study show that external factors which include economic aspects, the role of related institutions directly influence the internal factors of Songkok SMEs with the path coefficient value of 6.348. Where the economy is increasing, especially the surrounding community and the social sector, the role of relevant institutions in providing assistance in the procurement of business capital, production equipment, and marketing systems. External factors directly influence the competitiveness of Songkok Gresik SMEs with a path coefficient value of 2.883. Increase the growth of product sales, the growth in the number of workers so that they can absorb human resources around Songkok SMEs, market growth by expanding market segments that are owned so as to increase revenue growth.